Understanding sustainability in early childhood education case studies and approaches from across the UK - Boyd, Diane; Hirst, Nicky; Siraj-Blatchford, John 1952- (London Routledge, 2018)
"This unique book explores research related to education for sustainability within early childhood education in the United Kingdom. Divided into the four home nations, it examines what education for sustainability looks like in practice, discusses the different application and positions of each region, and considers the contribution of early childhood education to support the Sustainable Development Goals"--Provided by publisher.
1. Early Childhood Education for Sustainability within England -- 2. Early Childhood Education for Sustainability within Northern Ireland -- 3. Early Childhood Education for Sustainability within Scotland -- 4. Early Childhood Education for Sustainability within Wales -- 5. The Legacy of Maria Montessori -- 6. The legacy of Rudolf Steiner.
Keywords: Early childhood education -- Great Britain; Environmental education -- Great Britain; Sustainability